The MassGeneral Hospital for Children Adolescent Medicine Handbook - Goldstein, Mark A. (Springer International Publishing : Imprint: Springer, 2017)
The second edition of this definitive guide for clinical care of adolescents builds upon the practical knowledge and guidance of the first edition, and expands into new subjects of adolescent care. The handbook is divided into three sections: general adolescent medicine, sexuality, and mental health, and contains relevant, practical knowledge, covering those areas most often seen in the practice of adolescent medicine. The MassGeneral Hospital for Children Adolescent Medicine Handbook, 2nd edition details best practices in regards to diagnostic evaluations and clinical care, but also instructs practitioners on the best methods to connect, communicate, and continue that care with adolescents, in order to provide optimal treatment, and instill healthy lifetime behaviors. Each chapter is written by clinicians who have been trained at, or are members of the staff of Massachusetts General Hospital, and this edition has nearly doubled the amount of skilled physician authors. While this title has been revised and updated, entirely new chapters devoted to hypertension, immunizations, breast disorders, HIV, and resilience have also been added, reflecting new and changing contributions to the field of adolescent medicine. This second edition brings together the practical, hands-on knowledge of the first edition, along with new information and additional subject areas to create a balanced, multi-specialty method to treating and engaging adolescent patients.